ANTIOXIDANT CREAM FORMULATION OF PORANG TUBER ETHANOL EXTRACT AS AN ANTI-AGING AGENT - Ain Naia; Roy Indrianto Bangar; Hariyadi Dharmawan Syahputra (PT. Radja Intercontinental Publishing, 2026)
Irreversible skin aging begins in early adulthood due to intrinsic factors such as genetics and cellular metabolism and extrinsic factors such as ultraviolet exposure, smoking, pollution, and lifestyle, which trigger reactive oxygen species (ROS) and collagen damage, leading to wrinkles and reduced skin elasticity. This study aimed to formulate an optimal anti-aging cream from ethanol extract of porang tubers (Amorphophallus muelleri Blume) using variations in the HLB value of Span 60-Tween 80 emulsifiers. This quantitative experimental study used three cream formulas (F1: HLB 4.95; F2: HLB 5.7; F3: HLB 6.8) prepared from 3 kg of porang tubers obtained from Sirapit, Langkat. Evaluations included organoleptic properties, homogeneity, pH, viscosity, spreadability, adhesiveness, cycling-test stability, irritation, preference, and antioxidant activity using the DPPH method. The results showed that F2 was the optimal formula, with medium viscosity, spreadability of 6.2 cm², pH 5.8, stability for six cycles, and an IC₅₀ value of approximately 114 μg/mL, indicating moderate antioxidant activity. Formula F2 therefore has potential as a topical antioxidant preparation for preventing premature skin aging based on locally sourced tropical material.